Keutuhan permukaan AISI H13 keluli terkeras dalam proses pemesinan nyahcas elektrik (EDM) - Jaharah, A. Ghani; Goh, Geok Yong; Che Hassan, Che Haron; Ahmad Rasdan, Ismail; Baba, Md. Deros (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/